2019
DOI: 10.1186/s12893-019-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable reconstruction of the complex high-location bile duct injury: a novel hepaticojejunostomy

Abstract: BackgroundThis study aimed to propose a novel surgical reconstruction technique for complex high-location bile duct injury (CHBDI).MethodsThere were eight patients with CHBDI underwent the novel hepaticojejunostomy between Feb 2015 and Feb 2017. Seven patients underwent a primary operation and found CHBDI postoperatively in the inferior hospitals referred to our center. And four of them had received hepaticojejunostomy, but the results were not satisfying. One patient (No.8) with radiographically diagnosed hil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Familiarity with the porta hepatis during donor and recipient operations and small duct-to-duct biliary anastomoses using 7/0 sutures may have been responsible for these outcomes. 33 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familiarity with the porta hepatis during donor and recipient operations and small duct-to-duct biliary anastomoses using 7/0 sutures may have been responsible for these outcomes. 33 35 …”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with the porta hepatis during donor and recipient operations and small duct-to-duct biliary anastomoses using 7/0 sutures may have been responsible for these outcomes. [33][34][35] Liver resection is required in only 0.8% to 1.4% patients with complex vasculobiliary injury or proximal BDI. 12,17 A recent systematic review showed that only 67 patients underwent right hepatectomy for BDI.…”
Section: Discussionmentioning
confidence: 99%